Core-shell nanostructured organic redox polymer cathodes with superior performance. (October 2019) - Jia, He; Quan, Ting; Liu, Xuelian; Bai, Lu; Wang, Jiande; Boujioui, Fadoi; Ye, Ran; Vlad, Alexandru; Lu, Yan; Gohy, Jean-François
Abstract: Core-shell nanoparticles stabilized by a cationic surfactant are prepared from the poly(2, 2, 6, 6-tetramethylpiperidinyloxy-4-yl methacrylate) redox polymer. The nanoparticles are further self-assembled with negatively charged reduced graphene oxide nanosheets and negatively charged multi-walled carbon nanotubes. This results in the formation of a free-standing cathode with a layered nanostructure and a high content of redox polymer that exhibits 100% utilization of the active substance with a measured capacity as high as 105 mAh/g based on the whole weight of the electrode. Graphical abstract: Image 1 Highlights: - Free standing PTMA@CTAB@rGO@MWCNT composite electrodes have been prepared with electrochemical properties outperforming previous PTMA-based electrodes. - The stability of PTMA in the organic electrolyte is significantly improved with the protection of rGO shells. - When the cycling voltage range was extended from 2 V to 4 V, the composite electrodes show almost the highest specific capacity (105 mAh/g) reported so far for PTMA-based electrodes when normalized to the mass of the whole cathode.